(4,5-Diazafluoren-9-one-κ2N,N′)bis(thiocyanato-κS)mercury(II) - Behrouz Notash; Nasser Safari; Vahid Amani (Acta Crystallographica Section E, 2011)
In the title compound, [Hg(NCS)2(C11H6N2O)], the HgII atom, lying on a twofold rotation axis, is four-coordinated in a distorted tetrahedral geometry by an N,N′-bidentate diazafluoren-9-one ligand and two thiocyanate anions. In the crystal, intermolecular C—H...N and C—H...O hydrogen bonds are effective in the stabilization of the structure.